Molecular Modeling Suggests Cruzain Specificity for Peptide Primaquine Prodrugs - Goulart Trossini, Gustavo Henrique; Chin, Chung Man [UNESP]; de Souza Menezes, Carla Maria; Ferreira, Elizabeth Igne [UNESP] (Bentham Science Publ Ltd, 2010)
Chagas' disease, infection caused by the protozoan Trypanosoma cruzi, is an important, social and medical ailment in the Latin America. This disease is endemic in 21 countries, mostly Latin America countries, with more than 300,000 new cases every year and about 16-18 million infected people. Current therapy is not effective in the chronic phase of the disease. Thus, new and better drugs are urgently needed. In this sense, the in vitro activity of primaquine (PQ) was reported. Based on this, peptide prodrugs of primaquine containing dipeptides - lysine-arginine (LysArg), phenylalanine-alanine (PheAla) and phenylalanine-arginine (PheArg) -- as carriers, were designed to be selectively cleaved by cruzain, a specific cysteine protease of T. cruzi. The prodrugs have shown to be active against tripomastigote forms according to this order: LysArg-PQ> PheAla-PQ> PheArg-PQ. The molecular mechanism of action considered a probable nucleophilic attack of the catalytic residue of cruzain (Cys25) on the respective prodrug amide carbonyl carbon, releasing PQ. In order to test this hypothesis, molecular modeling studies were performed, physicochemical parameters and stereoelectronic features calculated by using the AM1 semi-empirical method suggest that the amide carbonyl carbon is favorable for cleavage, where the LysArg showed the most electronic reactive and sterically disposable, leading to the prodrug release and action. In addition, the docking study indicates the occurrence of specific interactions between prodrugs and the pockets S1 and S2 of cruzain through the dipeptides carriers, being the distance between cruzain Cys25 and the amide carbonyl group related to the biological activity of the prodrugs.
Keywords: Chagas' disease; Cruzain; Peptide prodrug; Molecular Modeling; AM1 semi-empirical method; Molecular docking